2015
DOI: 10.1371/journal.pone.0139524
|View full text |Cite
|
Sign up to set email alerts
|

HPV Prevalence in Multiple Anatomical Sites among Men Who Have Sex with Men in Peru

Abstract: BackgroundHuman Papilloma Virus (HPV) infection is the most common sexually transmitted viral infection worldwide. HPV is highly prevalent in sexually active men who have sex with men (MSM) and has been associated with anal cancer, penile cancer, and oropharyngeal cancer.MethodsFrom March to September 2011, we conducted a cross-sectional study of HPV prevalence among MSM above age 18 years. Participants were recruited using respondent driven sampling at Clinica Cayetano Heredia. All participants provided anal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
30
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 26 publications
14
30
1
2
Order By: Relevance
“…HPV infection was detected in about half of enrolled MSM who are considered as a vulnerable population for sexual transmitted infections, particularly for HPV‐attributable genital warts and anal cancer, in agreement with several reports . Prevalence was significantly lower in HIV uninfected subjects, in line with previous findings revealing an increased risk of infection in HIV positive homosexual men . In the present study, HIV infected MSM were estimated 2.5 at risk of acquiring HPV with respect to HIV uninfected ones, and similar results were previously reported for the anal site .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…HPV infection was detected in about half of enrolled MSM who are considered as a vulnerable population for sexual transmitted infections, particularly for HPV‐attributable genital warts and anal cancer, in agreement with several reports . Prevalence was significantly lower in HIV uninfected subjects, in line with previous findings revealing an increased risk of infection in HIV positive homosexual men . In the present study, HIV infected MSM were estimated 2.5 at risk of acquiring HPV with respect to HIV uninfected ones, and similar results were previously reported for the anal site .…”
Section: Discussionsupporting
confidence: 92%
“…Human Papillomavirus (HPV) is one of the most common sexually transmitted infection worldwide causing cervical cancer and other tumors in women, and anal, penile, oropharyngeal cancers in men . HPV is a transient infection with high rates of clearance, but persistence of high‐risk (HR) genotypes is demonstrated as a key factor for the development of cervical and anal cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Another study of HPV prevalence among 200 Peruvian MSM found the seroprevalence of HPV types 6/11/16/18-for which the quadrivalent HPV vaccine confers protectionwas 64.3% and 93.8% for HIV-negative and HIV-positive MSM, respectively. 25 While both studies included information related to sexual practices, identity and roles, the analyses conducted do not allow side-by-side comparisons of these factors and HPV, information which could inform HPV surveillance, prevention and treatment for Latino MSM.…”
Section: Open Accessmentioning
confidence: 99%
“…É uma doença transmitida sexualmente que pode desenvolver verrugas genitais, carcinoma de pênis, neoplasias intraperitoneais de pênis e câncer anal e de orofaringe (FREIRE E BLAS, 2014). Tem alta incidência em homens que se relacionam com homens (BLAS et al, 2014). Esse gênero é considerado um reservatório e um importante transmissor do vírus do HPV tanto para homens quanto para mulheres.…”
Section: Introductionunclassified